The Moral Hazard of Lifesaving Innovations: Naloxone Access, Opioid Abuse, and Crime - Jennifer Doleac; Anita Mukherjee (Institute of Labor Economics (IZA), 2018)
The United States is experiencing an epidemic of opioid abuse. In response, many states have increased access to naloxone, a drug that can save lives when administered during an overdose. However, naloxone access may unintentionally increase opioid abuse through two channels: (1) reducing the risk of death per use, thereby making riskier opioid use more appealing, and (2) saving the lives of active drug users, who survive to continue abusing opioids. By increasing the number of opioid abusers who need to fund their drug purchases, naloxone access laws may also increase theft. We exploit the staggered timing of naloxone access laws to estimate the total effects of these laws. We find that broadening naloxone access led to more opioid-related emergency room visits and more opioid-related theft, with no reduction in opioid-related mortality. These effects are driven by urban areas and vary by region. We find the most detrimental effects in the Midwest, including a 14% increase in opioid-related mortality in that region. We also find suggestive evidence that broadening naloxone access increased the use of fentanyl, a particularly potent opioid. While naloxone has great potential as a harm-reduction strategy, our analysis is consistent with the hypothesis that broadening access to naloxone encourages riskier behaviors with respect to opioid abuse.
Keywords: I18; K42; D81; 330; naloxone; opioids; moral hazard